Validierungsstudie zum Einsatz eines funklosen Brustgurtes - Sammito, S.; Sabine, D.; Böckelmann, I. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Background & Aim: In research and clinical medicine the interest in the heart rate variability (HRV) has increased in the recent past. With the variety of the measuring methods attention should he paid that all methods conform to the quality criteria's according the guideline of the DGAUM (DGAUM 2006). Heart-rate watch monitors have high failure rates when recording the heart rate in areas with electromagnetic interferences (Hottenrott, 2007) or inside of vehicles (Sammito, 2008). The aim of our study was the validation of a radio-less memory belt (Suunto Memory Belt [SMB]) for HRV recording under laboratory conditions and inside vehicles (medical ambulance vehicle [RTW] and an armoured military vehicle [MTW]) vs. a wire-lead transferring system (Schiller MT-101).